Inadequate fat diet - A. P. Levitsky; B. V. Egorov; A. P. Lapinskaya; I. A. Selivanskaya (Kazimierz Wielki University, 2020)
Aim. To determine the main factors of inadequate fat diet (IAFD) and indicate the ways of their change. Methods. Analysis and generalization of existing scientific literature data and the results of our own research. Results. The following factors of IAFD have been identified: 1) excess fat in the diet; 2) an excess of palmitic acid in dietary fats; 3) an excess of linoleic acid in dietary fats; 4) consumption of thermoperoxide fats; 5) deficiency of ω-3 polyunsaturated fatty acids (PUFA). Conclusion. IAFD is a cause of metabolic and neuropsychiatric disorders underlying non-communicable diseases.